(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Language-specific politeness techniques and certain verbal behaviours have been established by cultures. People in different nations use and interpret verbal behaviours somewhat differently depending on their pragmatic and sociolinguistic parameters.